A retrospective review of aortic Stenosis in 274 dogs in Scotland : clinical presentation and diagnosis - Machado, Alice Cristina Victorino (Universidade de Lisboa, Faculdade de Medicina Veterinária, 2018)
Dissertação de Mestrado Integrado em Medicina Veterinária. In the dog, aortic stenosis (AS) is classified as a congenital heart defect; however, its nature is progressive and some authors believe it to be acquired. In reviews, it has been reported as the most common congenital cardiac defect in Europe. Anatomically, it is classified as sub-valvular, valvular or supra-valvular. Boxers, Newfoundland dogs, Golden Retrievers, German Shepherds, are among the breeds considered to be predisposed to some forms of this defect. The present retrospective review encompasses 274 dogs with aortic stenosis, examined and diagnosed by a mobile cardiology referral practice in Scotland in a period of 11 years. Diagnostic classification, signalment, clinical, electrocardiographic, and echocardiographic features were obtained from records. A statistical analysis was performed in order to characterize the sample and to assess relationships between variables. The majority of the dogs in the sample were Boxers (40.51%), followed by Golden Retrievers (12.77%), Labrador Retrievers (6.20%) and German Shepherd Dogs (4.74%). Contrarily to current information, the anatomical classification of AS in this study was mostly valvular (47.08%), followed by sub-valvular fixed lesions (30.66%). There were 40.51% dogs with clinical signs at presentation, the most frequent motive for consultation was a recently detected heart murmur (46.72%), and the most common clinical sign at presentation was intolerance to exercise (27.44%), followed by syncope (24.45%). There were slightly more males (56.57%) than females in the sample and a relationship between haemodynamic severity and gender was established, as males were more severely affected than females. The mean age at presentation was three years, and the age of dogs in the sample ranged from one month to 14 years of age. Although it is a congenital defect, its progressive nature could contribute to this age distribution. Most dogs had murmurs on auscultation and murmur intensity was associated with ...